INVESTIGATION STUDENTS’ INTENSIVE LISTENING THROUGH CALL (COMPUTER ASSISTED LANGUAGE LEARNING) IN EFL CLASSROOM - Al-Baekani, Abdul Kodir (PEOPLE: International Journal of Social Sciences, 2019)
Listening is known as the process of identifying the sound sequences and also the process of identifying the component of sounds, whereby the words is known (Asemota, 2015). It can be seen as the process which is not only involving the process of hearing the sounds and noises, it also include identifying, understanding and interpreting spoken languages (Harrowoth, 1966, as cited in Asemota, 2015). In teaching and learning listening as foreign language using Intensive Listening usually relate to media. Media which have been used in teaching and learning foreign laguage is facilitated by technology, such as CALL (Computer Assisted Language Learning). This research of this situation is essential to conduct by researcher because Intensive Listening is listening practice that most teacher use in the classroom as a basic learning skill by investigating the process of learning and practising in the classroom or Language Laboratory. The researcher used qualitative research approach because the data in qualitative approach indicated the phenomenon in the school. The result of this research found that listening activities is needed to be applied intensively because most of respondent argued that listening activities through CALL as media brought the atmosphere of the class being enjoy, fun, and interesting.